Image zero-watermarking algorithm based on region of interest - ZHANG Li-bao; MA Xin-yue; CHEN Qi (Tongxin xuebao)
Based on ROI, a new watermarking algorithm was proposed.First, ROI was selected.Then, the wavelet transform was executed and ROI mask was constructed.Finally, the zero-watermarking was designed for the wavelet coefficients in ROI mask.The experimental results show that the zero-watermarking is more robust in the new algorithm than others that are not designed for ROI when the ROI of image is decoded at higher quality than the background.Additionally, the new algorithm can ensure ROI not to be disturbed by the watermarking information because of the zero-watermarking.